Pesticide Safety Miniposter: Protecting Yourself - Rebecca W. Baldwin; Stephanie K. Larrick Hill; Philip Koehler; W. Walker; J. C. Medley (EDIS, 2012)
To properly apply pesticides, a technician must be aware of the personal protective equipment, or PPE, required for the application. This poster introduces new pest control technicians to different types of PPE they may be required to wear during a pesticide application or pest management inspection. There is a wide array of examples of PPE on the poster, with quick response (QR) codes that direct smartphones to short, online videos explaining PPE for each area of the body (head, eyes, face, mouth, hands and arms, torso, and feet). This poster will serve as a valuable training tool for new technicians and a refresher tool for pest managers. Designed by R.W. Baldwin, S.K. Hill, Philip Koehler, W. Walker, and J.C. Medley, and published by the UF Department of Entomology and Nematology, August 2012.